2021
DOI: 10.1002/suco.202100061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber type and content on the mechanical properties and shrinkage characteristics of alkali‐activated kaolin

Abstract: An experimental study was carried out to evaluate the effect of several fibers on the mechanical properties, drying shrinkage, and microstructural characteristics of alkali‐activated kaolin binders. Four different types of fibers were evaluated in this study: polypropylene (PP) fiber, discontinuous structural synthetic (DSS) fiber, brass‐coated steel (BCS) fiber, and hooked steel (HS) fiber. The fibers were added to the alkali‐activated kaolin at a volume fraction of 0%, 0.5%, 1%, and 1.5%. The experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Fibers are used extensively in concrete production in order to controlling plastic shrinkage cracking of concrete 9,16,39,51 . It is aimed to improve the brittle characteristics of concrete such as crack formation resistance, weak tensile and flexural strength with fibers 9,52,53 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibers are used extensively in concrete production in order to controlling plastic shrinkage cracking of concrete 9,16,39,51 . It is aimed to improve the brittle characteristics of concrete such as crack formation resistance, weak tensile and flexural strength with fibers 9,52,53 .…”
Section: Introductionmentioning
confidence: 99%
“…It is aimed to improve the brittle characteristics of concrete such as crack formation resistance, weak tensile and flexural strength with fibers 9,52,53 . Natural and synthetic fibers such as glass, polypropylene (PP), basalt, steel, carbon are usually added to mixture as percentage of concrete volume 16,37,51,54 . PP fiber is the most popular one among all fibers 7,55,56 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the addition of fiber can significantly improve the flexural strength of concrete. 22,23 Researchers have also added polypropylene (PP) fiber to concrete to study the creep properties of concrete. 24,25 Haddad and Smadi 25 demonstrated that PP fiber was superior to steel fiber because of the lower fiber content required and lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the inhibitory effect of fiber on creep was strengthened by the increase in fiber content. Furthermore, the addition of fiber can significantly improve the flexural strength of concrete 22,23 . Researchers have also added polypropylene (PP) fiber to concrete to study the creep properties of concrete 24,25 .…”
Section: Introductionmentioning
confidence: 99%